2021
DOI: 10.3390/ijms22031309
|View full text |Cite
|
Sign up to set email alerts
|

Effect of O-Antigen Chain Length Regulation on the Immunogenicity of Shigella and Salmonella Generalized Modules for Membrane Antigens (GMMA)

Abstract: Recently, generalized modules for membrane antigens (GMMA) technology has been proposed as an alternative approach to traditional glycoconjugate vaccines for O-antigen delivery. Saccharide length is a well-known parameter that can impact the immune response induced by glycoconjugates both in terms of magnitude and quality. However, the criticality of O-antigen length on the immune response induced by GMMA-based vaccines has not been fully elucidated. Here, Shigella and Salmonella GMMA-producing strains were fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 43 publications
0
20
1
Order By: Relevance
“…One of these features is the saccharide length, a well-known parameter that can modulate the intensity and quality of immune response elicited by glycoconjugate vaccines. In contrast with what observed for traditional glycoconjugates, O-antigen length did not result to be a critical parameter for GMMA immunogenicity, independently by the pathogen and by the sugar structural characteristics (11). Moreover, we demonstrated that exposure of GMMA to high-temperature (100°C for 40 min) did not impact GMMA stability and immunogenicity in mice, whereas milder temperatures for a longer period of time did (37°C or 50°C for 4 weeks).…”
Section: Future Directionscontrasting
confidence: 88%
See 1 more Smart Citation
“…One of these features is the saccharide length, a well-known parameter that can modulate the intensity and quality of immune response elicited by glycoconjugate vaccines. In contrast with what observed for traditional glycoconjugates, O-antigen length did not result to be a critical parameter for GMMA immunogenicity, independently by the pathogen and by the sugar structural characteristics (11). Moreover, we demonstrated that exposure of GMMA to high-temperature (100°C for 40 min) did not impact GMMA stability and immunogenicity in mice, whereas milder temperatures for a longer period of time did (37°C or 50°C for 4 weeks).…”
Section: Future Directionscontrasting
confidence: 88%
“…Indeed, the entire production process from fermentation to final purified GMMA lasts 3 days and thus, depending on the size of the vaccine dose, a relatively small manufacture facility with a 500 L fermenter could produce 100 000 000 doses of vaccines per year at a manufacturing cost of approximately $1 per dose (10). GMMA from Shigella (4,5,7,9,(11)(12)(13), Salmonella (8,14,15), and Neisseria (16,18) species have been already generated using this approach, which is shown to be flexible enough to be potentially extended with minimal adjustments to any Gram-negative bacterial species. Indeed multiple industrial (17)(18)(19) and research (20)(21)(22) approaches based on genetic engineering of bacteria for hyper-vesiculating and surface-expression of a variety of homologous and heterologous antigens, including bacterial (20)(21)(22), viral (23), parasitic (24) and even cancer antigens (25) have been described.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, GMMA-producing strains can be easily mutated to display OAg with the desired features and resulting GMMA can be rapidly tested in animal studies. Here we have generated GMMA displaying S. flexneri 2a and 1b OAg with different O-acetylation patterns by knocking-out the responsible genes, similarly to what has already been reported to obtain different OAg size [43].…”
Section: Discussionmentioning
confidence: 91%
“…The serum samples used were polyclonal sera raised in mice or rabbits immunized with glycoconjugates (Vi-CRM197 [32,33] and O:2-CRM197 [34]), or with GMMA-based vaccines obtained from S. flexneri 1b, 2a, 3a, S. sonnei, S. Typhimurium and S. Enteritidis GMMA-producing strains [11,[24][25][26]31,35].…”
Section: Serum Samplesmentioning
confidence: 99%